Positive psychosocial factors and the development of symptoms of depression and posttraumatic stress symptoms following acute myocardial infarction - Zuccarella-Hackl, Claudia; Jimenez-Gonzalo, Lucia; von Känel, Roland; Princip, Mary; Jellestad, Lena; Langraf-Meister, Rebecca E.; Znoj, Hansjörg; Schmid, Jean-Paul; Barth, Jürgen; Schnyder, Ulrich; Ledermann, Katharina (Frontiers in Psychology, 2023)
Introduction Acute myocardial infarction (MI) is a potentially fatal condition, leading to high psychological distress and possibly resulting in the development of depressive symptoms and posttraumatic stress symptoms (PTSS). The aim of this study was to investigate the association of clusters of positive psychosocial factors (resilience, task-oriented coping, positive affect and social support) with both MI-induced depressive symptoms and PTSS, independent of demographic factors. Methods We investigated 154 consecutive patients with MI, 3 and 12 months after hospital discharge. All patients completed the short version of the German Resilience Scale, the Coping Inventory for Stressful Situations (CISS), the Enriched Social Support Inventory (ESSI) and the Global Mood Scale (GMS). The level of interviewer-rated MI-induced posttraumatic stress disorder (PTSD) symptoms at 3- and 12-months follow-up was evaluated through the Clinician-Administered PTSD Scale (CAPS). Depressive symptoms were assessed at 3- and 12-month follow-up with the Beck Depression Inventory (BDI-II). Results Three different clusters were revealed: (1) lonely cluster: lowest social support, resilience and average task-oriented coping and positive affect; (2) low risk cluster: highest resilience, task-oriented coping, positive affect and social support; (3) avoidant cluster: lowest task-oriented coping, positive affect, average resilience and social support. The clusters differed in depressive symptoms at 3 months (F = 5.10; p < 0.01) and 12 months follow-up (F = 7.56; p < 0.01). Cluster differences in PTSS were significant at 3 months (F = 4.78, p < 0.05) and 12 months (F = 5.57, p < 0.01) follow-up. Differences in PTSS subscales were found for avoidance (F = 4.8, p < 0.05) and hyperarousal (F = 5.63, p < 0.05), but not re-experiencing, at 3 months follow-up. At 12 months follow-up, cluster differences were significant for re-experiencing (F = 6.44, p < 0.01) and avoidance (F = 4.02, p < 0.05) but not hyperarousal. Discussion The present study contributes to a better understanding of the relationships among different positive psychosocial factors, depressive symptoms and PTSS following acute MI. Future interventions may benefit from taking into account positive psychosocial factors to potentially reduce patients’ depressive symptoms and PTSS after MI.